Jagged1 regulates extracellular matrix deposition and remodeling in triple-negative breast cancer - Parikainen, Marjaana; Suwal, Ujjwal; Rappu, Pekka; Heino, Jyrki; Sahlgren, Cecilia M. (American Association for the Advancement of Science (AAAS), 2026)
The extracellular matrix (ECM) and tumor microenvironment heterogeneity drive cancer progression and treatment resistance. High Jagged1 expression correlates with poor patient survival and promotes tumor growth and invasion in triple-negative breast cancer (TNBC). Using transcriptomics, proteomics, and imaging of cancer cell/fibroblast cocultures in vitro and in vivo, we demonstrate that Jagged1-mediated cross-talk between TNBC cells and fibroblasts enhances myofibroblast activation, collagen accumulation, and alignment of ECM fibers. In single-cell RNA sequencing data of TNBC tumors, high Jagged1 expression gives rise to a myofibroblast subpopulation previously associated with enhanced invasion. Jagged1 increases transforming growth factor–β (TGFβ) activity in fibroblast cocultures, and TGFβ inhibition prevents the Jagged1-induced ECM alignment. Thus, Jagged1 regulates ECM remodeling upstream of TGFβ. Furthermore, higher substrate stiffness up-regulates Jagged1, suggesting a feed-forward loop between Jagged1, ECM stiffness, and TGFβ. With the emergence of safe therapeutics targeting specific Notch components, Jagged1 modulation may offer an approach for treating invasive breast cancer.